Integrasi Budidaya Tanaman Kangkung (Ipomea Aquatica Forsk) dan Ikan Nila Menggunakan Internet of Things - Handayani, Murni; Sumardiono, Arif; Witriansyah, Khoeruddin; Fadillah (Infotekmesin, 2024)
Aquaponics is an application of a sustainable agricultural system by integrating the cultivation of plants and fish at one time. Water availability in plant commodities and water is optimized in aquaponic cultivation systems. Several parameters that can determine the level of success of cultivating an aquaponic system include water pH, water temperature, TDS, and water level. The process of monitoring and controlling several important parameters in cultivation can be done conventionally, but it is less effective and efficient because the cultivator has to check and measure the parameters every time. Therefore, as time goes by, and technology becomes more sophisticated, a control and monitoring system is designed. several parameters such as water pH, water temperature, TDS, and water level based on the Internet of Things (IoT) to support the success of the aquaponics system by monitoring environmental conditions using a laptop/smartphone at that time. Based on the test results, it was found that aquaponics in an indoor environment is successful - the air conditioner has a water temperature below 250C, the water pH shows 7pH and the average nutrient in the water shows 214.5 ppm. Based on this, kale plants in the stem grow quickly while leaf growth is very stunted. At temperatures smaller than 25 0C pomfret fish only survive for 2 weeks but tilapia fish can survive and not die in these environmental conditions. The length of the tilapia fish for 6 weeks has increased by 5 cm from its original length